Pengaruh Kepemimpinanl Transaksional, Komitmen Afektif, dan Kepuasan Kerja Terhadap Perilaku In – Role di Perusahaan Manufaktur Kab. Cirebon - Denada Putri; lImelda Aulia; Rahma Aulia Dita Rahayu (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Role-based behavior plays an important role in the company's components if a company wants its goals to be achieved. Employee involvement and participation can also influence individual employee performance, and ultimately have a very large impact on a company's success in achieving its goals. This research aims to analyze the influence of Transactional Leadership (X1), Affective Commitment (X2), and Job Satisfaction (X3) on Role-based Behavior (Y) at in the Manufacturing Company in Cirebon. The questionnaire was distributed to 60 respondents and the collected data was analyzed using SPSS version 27. The test results showed that Transactional Leadership has a significant positive effect on Role Behavior (T-count = 7.195; significance = 0.000), with a regression coefficient of 0.210. Affective Commitment has a significant positive effect on Role Behavior (T-count = 7.160; significance = 0.000), with a regression coefficient of 0.208. Job Satisfaction also has a significant positive effect on Role Behavior (T-count = 6.168; significance = 0.000), with a regression coefficient of 0.124. Simultaneous testing shows that Transactional Leadership, Affective Commitment, and Job Satisfaction together have a significant effect on Role Behavior (F-count = 230.733; significance = 0.000), with an Adjusted R-Square of 0.701.